Strategy Analysis in Translation of Film Subtitle in “Sing” Film - Maskuroh, Siti (Suara Bahasa, 2023)
Translation is very important for the development of science in all fields. This research take the object of translation in the subtitle of the film “SING”. The purpose of this research is to identify what translation strategies are contained in the subtitle of the film “SING”. What is the most dominant strategy and the accuracy of meaning and suitability for the duration of the film. This research is a qualitative descriptive study with purposive sampling technique. From research From this it can be seen that the translation strategy used in the film “SING” is a strategy addition, paraphrase, transfer, imitation, compression, decimation, deletion, and taming. In “SING” film, the most frequently used compression strategy. This is due to limitations the duration of space and time in the film so subtitles must save words. However, this is not reduce conformity with the meaning of the source language and still pay attention to the target culture. For words that are not in accordance with the target culture can be used taming strategiesKeywords: translation, subtitling, film “Sing”, translation strategy